Carbon neutrality cognition, environmental value, and consumption preference of low-carbon products - Li, Baoku; Nan, Yafeng; Yao, Ruoxi (Frontiers in Environmental Science, 2022)
It is now the mainstream scientific consensus that carbon emissions cause global climate change. Achieving the goal of China’s carbon neutrality is essential for environmental protection and economic sustainable development worldwide. In the above context, this paper aims to explore the carbon neutrality cognition, environmental value, and consumption preference for low-carbon products from the perspective of consumption end. Thus, we built and checked a new conceptual model of consumers’ carbon neutrality cognition and the consumption preference for low-carbon products. The TF-IDF algorithm in machine learning was used to confirm the dimensions of carbon neutrality cognition based on text data collected from an academic database CNKI. Then, we used data from a social investigation (N = 405) to test hypotheses and models using bootstrapping and independent sample t-tests. The results showed that altruistic (β = 0.168, 95% CI: [−0.54514, 0.8819]) and egoistic values (β = −0.066, 95% confidence interval [CI]: [−0.6361, 0.6772]) mediated the impact of carbon neutrality cognition on the consumption of low-carbon products, whereas the egoistic value did not (β = −0.066, 95% CI: [−0.6361, 0.6772]). Additionally, based on the characteristics of current Chinese consumers and the market, we argue for two boundary factors: face consciousness and carbon footprint label. The moderation of face consciousness (Mhigh = 5.395 vs. Mlow = 3.312) and carbon footprint label (Mwith = 6.394 vs. Mwithout = 5.432) were revealed. The empirical results support our conceptual model, and our findings provide insights to policymakers and enterprises regarding people’s carbon neutrality cognition, which will allow them to develop more appropriate policies and sustainable development strategies.